A Randomized, Placebo-Controlled Trial of Pentoxifylline on Erythropoiesis-Stimulating Agent Hyporesponsiveness in Anemic Patients With CKD: The Handling Erythropoietin Resistance With Oxpentifylline (HERO) Trial - Johnson, David W.; Pascoe, Elaine M.; Badve, Sunil V.; Dalziel, Kim; Cass, Alan; Clarke, Philip; Ferrari, Paolo; McDonald, Stephen P.; Morrish, Alicia T.; Pedagogos, Eugenie; Perkovic, Vlado; Reidlinger, Donna; et al. (American journal of kidney diseases, 2015)
Erythropoiesis-stimulating agent (ESA)-hyporesponsive anemia is common in chronic kidney disease (CKD). Pentoxifylline shows promise as a treatment for ESA-hyporesponsive anemia, but has not been rigorously evaluated. Multicenter, double-blind, randomized, controlled trial. 53 adult patients with CKD stage 4 or 5 (including dialysis) and ESA-hyporesponsive anemia (hemoglobin≤120g/L and ESA resistance index [calculated as weight-adjusted weekly ESA dose in IU/kg/wk divided by hemoglobin concentration in g/L]≥1.0IU/kg/wk/g/L for erythropoietin-treated patients and ≥0.005μg/kg/wk/g/L for darbepoetin-treated patients). Pentoxifylline (400mg/d; n=26) or matching placebo (control; n=27) for 4 months. Primary outcome: ESA resistance index at 4 months; secondary outcomes: hemoglobin concentration, ESA dose, blood transfusion requirement, serum ferritin level and transferrin saturation, C-reactive protein level, adverse events, quality of life, and health economics. There was no statistically significant difference in ESA resistance index between the pentoxifylline and control groups (adjusted mean difference, −0.39 [95%CI, −0.89 to 0.10] IU/kg/wk/g/L; P=0.1). Pentoxifylline significantly increased hemoglobin concentration relative to the control group (adjusted mean difference, 7.6 [95%CI, 1.7-13.5] g/L; P=0.01). There was no difference in ESA dose between groups (−20.8 [95%CI, −67.2 to 25.7] IU/kg/wk; P=0.4). No differences in blood transfusion requirements, adverse events, or quality of life were observed between groups. Pentoxifylline cost A$88.05 (US $82.94) per person over the trial and produced mean savings in ESA cost of A$1,332 (US $1,255). The overall economic impact over the trial period was a saving of A$1,244 (US $1,172) per person for the pentoxifylline group compared with controls. Sample size smaller than planned due to slow recruitment. Pentoxifylline did not significantly modify ESA hyporesponsiveness, but increased hemoglobin concentration. Further studies are warranted to determine whether pentoxifylline therapy represents a safe strategy for increasing hemoglobin levels in patients with CKD with ESA-hyporesponsive anemia.